IMPLEMENTATION OF BRIN REGULATION NO 5 OF 2023 AS AGRICULTURAL POLICY TO DEVELOP THE AGRICULTURAL SECTOR IN EAST KUTAI DISTRICT, EAST KALIMANTAN PROVINCE - Kurniadinata, Odit; Indana, Khairu (Agricultural Socio-Economics Journal, 2024)
Regulation of the National Research and Innovation Agency of the Republic of Indonesia (BRIN) Number 5 of 2023 concerning Governance of Research and Innovation in regions, replaces the Joint Regulation of the Minister of Research and Technology, and the Minister of Home Affairs of the Republic of Indonesia No. 3 of 2012 and no. 36 of 2012 concerning Strengthening Regional Innovation Systems. Increasing the productivity of national and regional competitiveness requires increasing innovative capacity and increasing regional competitiveness. The innovation system is an approach to economic development using science and technology that seeks to provide added value. Therefore, it is necessary to know how the BRIN regulations are implemented in East Kutai Regency regarding the development of the agricultural sector. This study was carried out using field survey and interview methods. Agriculture is one of the most strategic economic driving sectors in The existence and implementation of BRIN regulation no. 5 of 2023 can be said to accelerate the advancement of science and technology, especially the agricultural sector. With cooperation, integration, and harmonization of invention and innovation development programs carried out with relevant stakeholders as mandated in BRIN regulation no. 5 of 2023, there will be an acceleration in the preparation of Master Plan documents and Road Maps for the Advancement of Science and Technology, regarding the agricultural sector as economic transformation in the future.